Using an administrative primary care health activity indicator to address under-enumeration in the 2011 Census in Northern Ireland - Green, Brian; IJpelaar, Jos; Marshall, David; Beatty, Robert (Statistical and Social Inquiry Society of Ireland, 2014)
Despite the fact that the Census Act (Northern Ireland) 1969 places a legal obligation on everyone in the Country to take part in the Census, not everyone does. This gives rise to under-enumeration, which is not unique to the Census in Northern Ireland. In Northern Ireland it is Census policy, in line with arrangements throughout the rest of the UK, that Census estimates should cover the entire population. Accordingly, Census Office is required to address any under-enumeration in the Census by imputing any details that have been missed. This paper outlines how NISRA utilised an administrative Primary Care health activity indicator to supply real demographic information (rather than modelled information) for some of the households who failed to respond to the Census. In addition, it highlights how critical design aspects of the 2011 Census were tailored in order to facilitate the approach, which has attracted considerable interest both nationally and internationally and is considered to have improved the overall quality of the 2011 Census estimates in Northern Ireland.
Keywords: Census; under-enumeration; sign-of-life; address; real; demographic activity; administrative; Primary Care; health; indicator; indicator; CUE; Northern Ireland; prescription; dentist; optician; 314.15